2007
DOI: 10.1136/thx.2006.075937
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in sputum neutrophil and eosinophil numbers by the PDE4 inhibitor roflumilast in patients with COPD

Abstract: Background: Roflumilast is a targeted oral once-daily administered phosphodiesterase 4 (PDE4) inhibitor with clinical efficacy in chronic obstructive pulmonary disease (COPD). Results from in vitro studies with roflumilast indicate that it has anti-inflammatory properties that may be applicable for the treatment of COPD. Methods: In a crossover study, 38 patients with COPD (mean (SD) age 63.1 (7.0) years, post-bronchodilator forced expiratory volume in 1 s (FEV 1 ) 61.0 (12.6)% predicted) received 500 mg roflu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
177
0
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(192 citation statements)
references
References 37 publications
9
177
0
6
Order By: Relevance
“…A selective PDE4 inhibitor, roflumilast, inhibits lung inflammation and emphysema in a smoking model of COPD in mice [202]. In COPD patients, oral roflumilast given over 4 weeks significantly reduces the number of neutrophils (by 36%) and CXCL8 concentrations in sputum [203]. In clinical trials, roflumilast given over 6 or 12 months improves lung function in COPD patients to a small extent but has no significant effect in reducing exacerbations or improving health status [204,205].…”
Section: Pde4 Inhibitorsmentioning
confidence: 99%
“…A selective PDE4 inhibitor, roflumilast, inhibits lung inflammation and emphysema in a smoking model of COPD in mice [202]. In COPD patients, oral roflumilast given over 4 weeks significantly reduces the number of neutrophils (by 36%) and CXCL8 concentrations in sputum [203]. In clinical trials, roflumilast given over 6 or 12 months improves lung function in COPD patients to a small extent but has no significant effect in reducing exacerbations or improving health status [204,205].…”
Section: Pde4 Inhibitorsmentioning
confidence: 99%
“…The mortality due to COPD was similar in both treatment-arms in both studies The mechanism of the improvements in lung function, exacerbation rates and quality of life scores cannot be attributed to a direct bronchodilating action of this drug class, as we have previously discussed for cilomilast. It is more likely that these beneficial actions are secondary to an anti-inflammatory activity of roflumilast, although the reduction in pro-inflammatory cell numbers found in two other studies was modest, reflecting a 30-50% suppression of inflammatory cell numbers [43,44] and reduced the number of airway CD8+ T lymphocytes and CD68+ macrophages by approximately 40-50% [30]. Other evidence of an anti-inflammatory mechanism stems from in vitro studies which reported that cilomilast reduced the level of TNF-alpha (25% decrease), GMCSF (46% decrease) and neutrophil chemotactic factors (35% decrease) with no effect on IL-8 released by epithelial cells from COPD patients [45].…”
Section: Roflumilast: Pharmacokinetics Clinical Efficacy From Phase mentioning
confidence: 90%
“…Indeed, roflumilast treatment alone failed to significantly increase macrophage and neutrophil cell number in the lung in a preclinical model of smoke-induced inflammation, but reduced the rise in macrophage and neutrophil cell numbers caused by cigarette smoke exposure [18,66]. Similarly, human clinical data shows that the PDE4-inhibitors, cilomilast and roflumilast, reduce inflammatory cell numbers in the lung compartment [43,67]. In conclusion, ample evidence has been provided that the PDE4-inhibitors cilomilast and roflumilast, at a clinically relevant dose, are capable of reducing airway inflammation.…”
Section: Adverse Events During Long-term Pde4-inhibitionmentioning
confidence: 98%
“…Despite that chronic cough and sputum production are characteristics of bronchiectasis, they have been suggested as a risk factor for exacerbations of COPD (68,69). Roflumilast has been shown benefit for inhibiting neutrophilic airway inflammation in COPD and preventing exacerbation in COPD with chronic bronchitis (46,54). In addition, neutrophils are prominent cell type involved in bronchiectasis and neutrophilic inflammation is key pathogenesis of COPD (70)(71)(72).…”
Section: Clinical Evidence Of the Efficacy Of Roflumilast In Other Aimentioning
confidence: 99%
“…Another placebo-controlled study showed roflumilast decreased sputum cell counts, both eosinophils and neutrophils. In addition to its effect on inflammatory cells, roflumilast reduced neutrophilic and eosinophilic inflammatory mediators in sputum of COPD patients (46). The difference between the efficacy of cilomilast and roflumilast is associated with the different IC 50 ; roflumilast is more potent than cilomilast for PDE4B inhibition in inflammatory cells (35).…”
Section: Clinical Evidence Of the Efficacy Of Roflumilast In Copdmentioning
confidence: 99%